2011
DOI: 10.1016/j.ophtha.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Macular Ganglion Cell Layer Imaging in Preperimetric Glaucoma with Speckle Noise–Reduced Spectral Domain Optical Coherence Tomography

Abstract: Proprietary or commercial disclosure may be found after the references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 34 publications
4
60
0
1
Order By: Relevance
“…However, Curcio et al also reported that the macular RGC density is not completely symmetrical: the temporal RGC density was slightly lower than the nasal RGC density, whereas the inferior and superior RGC densities were almost equivalent. 1 Nakano et al 13 measured the GCL thickness on SD-OCT images and found identical symmetry between the macular GCL thickness and the RGC density; that is, the temporal GCL was thinner than the nasal GCL, while the superior and inferior GCL thicknesses were almost equivalent. Therefore, we estimated the variability of GCIPL measurements among 360 spokes and found mild variations (maximum difference, 12% of average GCIPL thickness on 360 spokes) among 360 spokes even in healthy eyes.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…However, Curcio et al also reported that the macular RGC density is not completely symmetrical: the temporal RGC density was slightly lower than the nasal RGC density, whereas the inferior and superior RGC densities were almost equivalent. 1 Nakano et al 13 measured the GCL thickness on SD-OCT images and found identical symmetry between the macular GCL thickness and the RGC density; that is, the temporal GCL was thinner than the nasal GCL, while the superior and inferior GCL thicknesses were almost equivalent. Therefore, we estimated the variability of GCIPL measurements among 360 spokes and found mild variations (maximum difference, 12% of average GCIPL thickness on 360 spokes) among 360 spokes even in healthy eyes.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies using SD-OCT showed similar symmetrical thicknesses of the GCL, IPL, and GCLþIPL of healthy eyes in an elliptical annulus. 7,10,13,19,26 The GCIPL thicknesses on all 360 spokes should be equivalent if the symmetry is perfect; and, consequently, the initial RGC loss limited to a small local area would be detectable as a decrease of the GCIPL thickness on the spokes, leading to minimum GCIPL thickness. Thus, this parameter should theoretically detect early or initial RGC loss with high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations